Pertimbangan Hakim dalam Menjatuhkan Putusan Pidana terhadap Terdakwa atas Kepemilikan Senjata Api Tanpa Izin - Aprido Ariyandi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
A crime is an act prohibited by law, and anyone who commits an act that violates the law will be punished. Furthermore, a crime is also a form of violation of social norms. Violations are determined within the limits of values ??upheld in a society. The law is not the goal, but merely a bridge or tool that will lead us to the desired idea. The widespread use of firearms today can start from simply showing off, acting like a hero, to actions that can even lead to threats and even murder. This is truly a frightening event and threatens the peace of society. Another motive for the misuse of firearms is illegal ownership for certain purposes. Owning a firearm does not mean it is not permitted; everyone who owns and uses a firearm must meet the requirements and obtain permission from the authorized institution. The problems in writing this thesis are: How is the process of granting a firearm ownership permit according to the demands stipulated in Law Number 8 of 1948? What are the judge's considerations in handing down a criminal sentence against a defendant who possesses a firearm without a permit. In accordance with Decision Number 368/pid.sus/2024/PN.Tjk. This research method uses a normative and empirical juridical approach. The types of data used are secondary data and primary data. Data collection through library research and field research. The data analysis used is qualitative juridical. Based on the results of Article 5 of Law Number 8 of 1948 concerning Registration and Granting of Firearms Use Permits, it is explained that firearms in the hands of people who are not members of the Army or Police must be registered by the Head of the Residency (or the Head of the Regional Police hereinafter referred to as the Head of the Residency Police) or the person designated by him